Harley, R.M., Antar, G.M. & Giulietti, A.M. (2019) Erratum for “Stachytarpheta atkinsiae, A new species of Verbenaceae endemic to the Chapada Diamantina, Bahia, Brazil” Phytotaxa 401 (2): 127–132. - Harley, Raymond M.; Antar, Guilherme Medeiros; Giulietti, Ana Maria (Phytotaxa, 2019)
Nil